2017
DOI: 10.2147/dddt.s151660
|View full text |Cite
|
Sign up to set email alerts
|

The oral bioavailability, excretion and cytochrome P450 inhibition properties of epiberberine: an in vivo and in vitro evaluation

Abstract: Epiberberine (EPI) is a novel and potentially effective therapeutic and preventive agent for diabetes and cardiovascular disease. To evaluate its potential value for drug development, a specific, sensitive and robust high-performance liquid chromatography-tandem mass spectrometry assay for the determination of EPI in rat biological samples was established. This assay was used to study the pharmacokinetics, bioavailability and excretion of EPI in rats after oral administration. In addition, a cocktail method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…CYP450-mediated drug–drug interaction is one of the important reasons for the dropout of drug candidates during new drug development . Therefore, testing for drug–drug interaction potential of new chemical entities is essential for developing a novel drug. As a result, compounds 24w and 25w were selected to further evaluate their in vitro inhibitory potential of major CYP450 enzymes including CYP1A2, CYP2A6, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4 in a CYP450 inhibition cocktail assay, and the results are summarized in Table . Indeed, compound 25w was found to show no significant inhibition against these CYP450 isoforms at 10 μM, which indicated that its IC 50 value against these major CYP450 isoforms was greater than 10 μM.…”
Section: Resultsmentioning
confidence: 97%
“…CYP450-mediated drug–drug interaction is one of the important reasons for the dropout of drug candidates during new drug development . Therefore, testing for drug–drug interaction potential of new chemical entities is essential for developing a novel drug. As a result, compounds 24w and 25w were selected to further evaluate their in vitro inhibitory potential of major CYP450 enzymes including CYP1A2, CYP2A6, CYP2C9, CYP2C19, CYP2D6, CYP2E1, and CYP3A4 in a CYP450 inhibition cocktail assay, and the results are summarized in Table . Indeed, compound 25w was found to show no significant inhibition against these CYP450 isoforms at 10 μM, which indicated that its IC 50 value against these major CYP450 isoforms was greater than 10 μM.…”
Section: Resultsmentioning
confidence: 97%
“…Obacunone, as one of the oxygenated triterpenoids of Huang Lian, has been confirmed to be beneficial against obesity through the Takeda G-protein receptor 5 (TGR5) and peroxisome proliferator–activated receptor gamma (PPARγ) pathway (Horiba et al, 2015). The protoberberine alkaloid epiberberine (OB = 43.09% and DL = 0.78) from Huang Lian is a potential preventive and therapeutic agent for diabetes (Chen et al, 2018). Calycosin is the major active component in Huang Qi and exhibits beneficial effects against high-fat diet-induced nonalcoholic fatty liver disease (Duan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Berberine and other alkaloids, including jatrorrhizine and palmatine, can be metabolized by CYP3A4, CYP1A2 and CYP2D6 [27][28][29][30]. These enzymes can also be inhibited by epiberberine and berberine [31][32][33][34]. Thus, there might be drug-drug interactions (DDIs) between these alkaloids, A sex difference was also observed for the plasma concentrations of the compounds.…”
Section: Discussionmentioning
confidence: 99%